1992
DOI: 10.1016/1044-0305(92)87066-8
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of atmospheric pressure ionization techniques for the analysis of N-Methyl carbamate pesticides by liquid chromatography mass spectrometry

Abstract: Atmospheric pressure ionization (API) techniques are evaluated for the mass spectral analysis of N-methyl carbamate pesticides. Atmospheric pressure chemical ionization (APCI) using a heated nebulizer interface provided both protonated molecules and abundant, characteristic fragment ions. With ion spray (ISP; pneumatically assisted electrospray ionization), which utilizes a milder "ion evaporation" process, primarily protonated molecules were obtained, although fragment ions similar to those observed in APCI c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
31
1

Year Published

1995
1995
2000
2000

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(34 citation statements)
references
References 30 publications
2
31
1
Order By: Relevance
“…Of these, the majority used atmospheric pressure chemical ionization (APCI). 1 Pleasance et al 2 evaluated APCI, ionspray (ISP) (pneumatically assisted electrospray), thermospray (TSP) and particle-beam interfaces for the detection of carbamate pesticides and found that APCI provided superior results. We have successfully used both APCI and ISP for the determination of a variety of pesticides, and have recently reported on the use of ISP for multi-residue analyses.…”
mentioning
confidence: 98%
“…Of these, the majority used atmospheric pressure chemical ionization (APCI). 1 Pleasance et al 2 evaluated APCI, ionspray (ISP) (pneumatically assisted electrospray), thermospray (TSP) and particle-beam interfaces for the detection of carbamate pesticides and found that APCI provided superior results. We have successfully used both APCI and ISP for the determination of a variety of pesticides, and have recently reported on the use of ISP for multi-residue analyses.…”
mentioning
confidence: 98%
“…Doerge and Bajic 7 evaluated the use of APCI-MS for several classes of pesticides, including ASon and CBF, and applied the technique to the analysis of triazine herbicides in water. Pleasance et al 8 evaluated APCI and ESI for the analysis of N-methyl carbamate pesticides (including ALD, ASon, ASox, CBF and 3-OH-C) and compared these techniques with TSP and with particle beam interfacing using electron ionization. Of the 4 techniques APCI had a clear advantage over the other techniques with respect to sensitivity, linearity and range of applicability to all the carbamates studied.…”
mentioning
confidence: 99%
“…NCI of carbamates has not been systematically investigated, although there are indications from APCI experiments that NCI is not so well suited for carbamates. 13 In order to investigate the feasibility of CI for carbamate detection with a PB inlet system, we tested 33 analytes (shown in Table 2), under PCI and NCI conditions using methane and ammonia. Special attention was devoted to the inÑuence of ion source temperature and gas pressure on the appearance of spectra.…”
Section: Chemical Ionizationmentioning
confidence: 99%